Adsorption Behaviour of Co(II) from Aqueous Solutions onto D113-III Resin - Jiang, Xinlong; Yang, Liqun; Yang, Qing; Xiong, Chunhua; Jiang, Jianxiong; Jia, Qian; Chen, Qing (Asian Journal of Chemistry, 2014)
In this study, the adsorption and desorption properties of Co(II) on D113-III resin have been studied. The different variables affecting the adsorption capacity such as pH of the solution, temperature and contact time have been investigated, which indicate that D113-III resin could adsorb Co(II) effectively from aqueous solution. The results show that the optimal adsorption condition of D113-III resin for Co(II) is achieved at pH = 6.5. The maximum saturated adsorption capacity of Co(II) is 192.1 mg g-1 D113-III resin at 298 K. The thermodynamic parameters such as DGo which were all negative and DHo which was positive, indicated that the adsorption of Co(II) ion onto D113-III resin was spontaneous and endothermic, respectively. Positive DSo value of Co(II) adsorption process indicates an irregular increase of the randomness at the D113-III resin-solution interface during adsorption. Adsorption isotherms correlated well with the Langmuir model. Experimental data were also evaluated to find out kinetic characteristics of the adsorption process. Desorption studies revealed that Co(II) ion could be eluted effectively by using the 0.25-1.0 mol L-1 HCl solution. Thomas model was applied to experimental data to predict the breakthrough curves and to determine the characteristics parameters of the column useful for process design.